Extraction of the Contours of Optic Disc and Exudates Based on Marker-Controlled Watershed Segmentation - C., Eswaran; Ahmed Wasif, Reza; Subhas, Hati (2008)
The optic disc (OD) and exudates form the main features of fundus images for diagnosing eye diseases such as diabetic retinopathy and glaucoma. In this paper, an algorithm for the extraction of OD and exudates from fundus images based on marker-controlled watershed segmentation is presented. The proposed algorithm makes use of average filtering and contrast adjustment as preprocessing steps before the watershed transformation is applied The performance of the proposed algorithm is evaluated using the test images of STARE and DRIVE databases. The results are compared with those reported earlier in the literature. It is shown that the proposed method can yield an average sensitivity value of 94%, which is higher than the value reported earlier.